Case Study in Watershed Researc - Mishra, P. R.; Dayal, Rajhans; Bhola, S. N. (Indian Forester, 1967)
The Importance of case study in watershed research has been discussed in this paper. It is an important tool to explain the complex interrelationship between various factors and processes towards developing clearer understanding to the functioning of a watershed under different land treatments. Case study as an important tool of Scientists in invention and discovery, its wide adoption as a scientific method of research in some of the biological sciences, its scope in watershed research and its advantages over statistical method of research have been high-lighted. The paper advocates its adoption in watershed research.